MOBILITY, BRAIN BLOOD FLOW, SYSTEMIC INFLAMMATION AND, CARDIAC AND ARTERIAL STIFFNESS IN COGNITIVELY NORMAL ELDERS. (11th November 2018) - Nadkarni, N; Snitz, B; Perera, S; Cohen, A; Lopresti, B; Barinas-Mitchell, E; Klunk, W; Lopez, O
Abstract: Background: Gait speed is associated with cerebral amyloid-β deposition and inflammation in cognitively normal older adults (CNOA). Whether gait speed is associated with cerebral blood flow (CBF) and, cardiac and arterial stiffness remains unknown. Aim: We examined the cross-sectional association between gait speed, amyloid-β, CBF, inflammation and, cardiac and arterial stiffness in CNOA. Method: We assessed gait speed on 15'walks, amyloid-β on PiB-PET, CBF on ASL-MRI, inflammation using serum sCD14 and TNF-R1 levels, cardiac stiffness on QRS-voltage on EKG and arterial stiffness using carotid-femoral pulse-wave velocity (PWV). Statistical methodology included Pearson's correlations and regression analyses. Results: In this population (N=65, mean age: 85.7 years, 69% female), gait speed correlated with global PiB retention (r=-0.26, p=0.038), global CBF (r=-0.26, p=0.036), TNF-R1 (r=-0.24, p=0.05) and sCD14 (r=-0.19, p=0.039) levels, carotid-femoral PWV (r=-0.27, p=0.05, n=51) and QRS-voltage (r=0.35, p=0.007). QRS-voltage correlated with TNF-R1 levels (r=-0.29, p=0.027). Gait speed and sCD14 levels significantly correlated with anterior cingulate CBF (r=-0.31, p=0.019 and r=0.27, p=0.28) and occipital CBF (r=-0.27, p=0.025 and r=0.3, p=0.015). Slower gait was associated with lower QRS-voltage (β=0.36, p=0.012) despite adjustment for demographics, BMI, TNF-R1 levels and hypertension (β=0.3, p=0.034), but not APOE-e4 carrier status (β=0.25, p=0.084). The association between slower gait and, increased global CBF (β=-0.37, p=0.011) and increased carotid-femoral PWV (β=-0.31, p=0.041), remained significant after above adjustments. Conclusion: In the face of deleterious changes in the aging brain, heart, arteries and systemic inflammation influencing gait speed, CNOA may develop an auto-regulatory increase in CBF, which is likely a maladaptive compensatory response.